일개 의과대학 학생들의 개인적 특성에 따른 팀바탕학습 인식도 조사 - 박귀화(Kwi Hwa Park); 최창휴(Chang Hyu Choi); 전양빈(Yang Bin Jeon); 박국양(Kook Yang Park); 박철현(Chul Hyun Park) (Korean journal of medical education, 2013)
Purpose: The purpose of this study was to examine medical students’ perceptions of team-based learning (TBL) according to their individual characteristics: gender, team efficacy, interpersonal understanding, proactivity in problem solving, and academic ability. Methods: Thirty-eight second-year medical students who took an integrated cardiology course participated in this study; 28 were male and 10 were female. A questionnaire on individual characteristics and a questionnaire on the perception of TBL were administered, and the scores of individual characteristics were grouped into three: high, middle, and low. The data were analyzed by t-test, analysis of variance, and multiple regression analysis. Results: The TBL efficacy perception scale consisted of 3 factors: team skill, learning ability, and team learning. The group of male students and the group of students with high academic ability recognized the effect of TBL on improvements in learning ability more than females and those with low academic ability. The group of students with high team efficacy reported that TBL was effective with regard to team skill improvement. The group of students with high scores on interpersonal understanding and high proactive problem solving tended to perceive the TBL's effect on team skill improvement. Team efficacy and proactivity in problem solving had a positive effect on the perception of TBL. Conclusion: Medical students’ perceptions of the effectiveness of TBL differ according to individual characteristics. The results of this study suggest that these individual characteristics should be considered in planning of team learning, such as TBL, to have a positive impact and stronger effects. KCI Citation Count: 12